Hepatitis C virus mediated chronic inflammation and tumorigenesis in the humanised immune system and liver mouse model. - Zhiqiang Zheng; Ching Wooen Sze; Choong Tat Keng; Muthafar Al-Haddawi; Min Liu; Sue Yee Tan; Hwee Ling Kwek; Zhisheng Her; Xue Ying Chan; Bhaskar Barnwal; Eva Loh; Kenneth Tou En Chang; et al. (PLoS ONE)
Hepatitis C is a liver disease caused by infection of the Hepatitis C virus (HCV). Many individuals infected by the virus are unable to resolve the viral infection and develop chronic hepatitis, which can lead to formation of liver cirrhosis and cancer. To understand better how initial HCV infections progress to chronic liver diseases, we characterised the long term pathogenic effects of HCV infections with the use of a humanised mouse model (HIL mice) we have previously established. Although HCV RNA could be detected in infected mice up to 9 weeks post infection, HCV infected mice developed increased incidences of liver fibrosis, granulomatous inflammation and tumour formation in the form of hepatocellular adenomas or hepatocellular carcinomas by 28 weeks post infection compared to uninfected mice. We also demonstrated that chronic liver inflammation in HCV infected mice was mediated by the human immune system, particularly by monocytes/macrophages and T cells which exhibited exhaustion phenotypes. In conclusion, HIL mice can recapitulate some of the clinical symptoms such as chronic inflammation, immune cell exhaustion and tumorigenesis seen in HCV patients. Our findings also suggest that persistence of HCV-associated liver disease appear to require initial infections of HCV and immune responses but not long term HCV viraemia.